Precautionary Fertility: Conceptions, Births, and Abortions around Employment Shocks - Anna Bárdits; Anna Adamecz-Völgyi; Márta Bisztray; Andrea Weber; Agnes Szabó-Morvai (Institute of Labor Economics (IZA), 2023)
We study fertility responses to employment shocks. Using unique Hungarian administrative data that allow linking firm-level mass layoff and closure events to individual-level records on births and abortions, we show that the main response happens in anticipation of the shock. Responses differ by the availability of dismissal protection. While pregnancies increase in anticipation of all events, births only rise in case of mass layoffs when pregnant women are protected from layoffs. If the firm closes protection is lost and we find an increase in abortions. We interpret these results as evidence for precautionary fertility behavior. Women threatened by job displacement bring births forward to exploit dismissal protection, a strategy that breaks down if the firm closes permanently.
Keywords: I12; J13; J65; 330; abortion; birth; pregnancy; mass layoff; firm closure